Pathogenesis of chronic pancreatitis (2008)
Chronic Pancreatitis is characterized by progressive and irreversible damage of the pancreas, many etiologies are known but chronic alcohol ingestion is the primary cause. Recently there have been important advances in knowledge of the pathogenesis of alcohol damage. Important advances have also been made in regard to the mechanisms of pancreatic fibrinogenesis and the role of the stellate cells in the fibrosis of this disease. Genetic mutations involved in the process of activation/inactivation of trypsinogen in the pancreas, and other mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) that affect bicarbonate secretion, have been described as related to the development of chronic Pancreatitis of different etiologies such as idiopathic, alcoholic and tropical Pancreatitis. © 2008 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.